2007
DOI: 10.1007/s10826-006-9120-3
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing Symptoms and Affective Reactivity in Relation to the Severity of Aggression in Clinically Referred, Behavior-Disordered Children

Abstract: We examined the affective correlates of aggression in children referred to a partial hospitalization program for the treatment of behavior disorders who did not have a mood or anxiety disorder. Parent and teacher ratings of the children's impulsivity, internalizing symptoms, affective reactivity, and aggression were examined for their interrelationships and then entered into regression analyses to predict the child's level of aggression in the home, at school, and in the treatment program. Intercorrelations am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Second, diagnostic questions about pediatric bipolar disorder also highlight the relative paucity of research on irritability: operationalized definitions, reliable rating scales (although see references 2325), and normative data are all sparse. In fact, DSM-IV provides no definition of irritability, despite the inclusion of this symptom as a criterion for at least six diagnoses in children (manic episode, oppositional defiant disorder, generalized anxiety disorder, dysthymic disorder, posttraumatic stress disorder, and major depressive episode).…”
Section: Defining Severe Mood Dysregulationmentioning
confidence: 99%
“…Second, diagnostic questions about pediatric bipolar disorder also highlight the relative paucity of research on irritability: operationalized definitions, reliable rating scales (although see references 2325), and normative data are all sparse. In fact, DSM-IV provides no definition of irritability, despite the inclusion of this symptom as a criterion for at least six diagnoses in children (manic episode, oppositional defiant disorder, generalized anxiety disorder, dysthymic disorder, posttraumatic stress disorder, and major depressive episode).…”
Section: Defining Severe Mood Dysregulationmentioning
confidence: 99%
“…Second, diagnostic questions about pediatric bipolar disorder also highlight the relative paucity of research on irritability: operationalized definitions, reliable rating scales (although see references [23][24][25], and normative data are all sparse. In fact, DSM-IV provides no definition of irritability, despite the inclusion of this symptom as a criterion for at least six diagnoses in children (manic episode, oppositional defiant disorder, generalized anxiety disorder, dysthymic disorder, posttraumatic stress disorder, and major depressive episode).…”
Section: Defining Severe Mood Dysregulationmentioning
confidence: 99%
“…Increased reactivity has been linked to both anxiety (Carthy et al 2010a, b) and aggression (Valiente et al 2003). Although aggression and anxiety together can be related to strong emotional reactivity (e.g., Kolko et al 2007), several research studies have demonstrated that anxiety and aggression are also associated with specific emotional responses to provocation. For example, Stadler et al (2006) found that larger affective arousal (i.e., self-reported anger following a provocation), but not physiological arousal (i.e., changes in skin conductance or heart rate), significantly predicted aggression in a sample of children ages 9-14.…”
Section: Emotional Reactivitymentioning
confidence: 99%